Optimal reconfiguration of distribution network - Rajesh Kumar, V.; Sai Kiran, V. (International Journal of Engineering and Technology, 2018)
Â This paper proposes a simple method for solving the distribution system reconfiguration to improve the voltage profile and reduce the losses. In this paper power flow studies are used in matrix form of distribution system with radial, weakly meshed and reconfigured forms. The execution of power flow will specify the bus voltages and branch currents. These parameters are used to analyse the system performance and especially branch currents information is used to convert system radial form to weakly meshed and reconfiguration forms by closing the tie-switches and opening the sectionalizing switches. The same information can be used in large networks to show the improvement in voltage profile and reduction in electrical losses.Â Â